2011
DOI: 10.1177/104063871102300201
|View full text |Cite
|
Sign up to set email alerts
|

Change in Predominance ofBovine Viral Diarrhea VirusSubgenotypes among Samples Submitted to a Diagnostic Laboratory over a 20-Year Time Span

Abstract: Abstract. Although the causative agent of bovine viral diarrhea was initially categorized as 1 species, phylogenetic analysis revealed that these viruses belong to 2 different species, Bovine viral diarrhea virus 1 (BVDV-1) and BVDV-2, with 2-11 subgenotypes within each species. Distribution of species and subgenotypes has been shown to vary with geographic region. Whether distribution shifts over time is not known. Surveys conducted between 1994 and 2008 reported 3 subgenotypes circulating among cattle in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 29 publications
0
34
0
2
Order By: Relevance
“…Bovine viral diarrhea viruses (BVDV) are enveloped singlestranded positive-sense RNA viruses comprised of two species, BVDV1 and BVDV2, in the Flaviviridae family (Driskell and Ridpath, 2006;Ridpath et al, 2011). The BVDV genome is approximately 12.5 kb in length and is organized into 12 genes flanked by a Abbreviations: BRDC, bovine respiratory disease complex; BVDV, bovine viral diarrhea virus; CP, cytopathic; HV, high virulence; IFN␥, interferon gamma; IL-6, interleukin 6; LPS, lipopolysaccharide; LV, low virulence; MDM , monocyte derived macrophage; MyD88, myeloid differentiation primary response gene 88; NCP, non-cytpathic; NS5A, non-structural protein 5A; qPCR, quantitative (real-time) polymerase chain reaction; TLR, toll like receptor; TNF␣, tumor necrosis factor alpha; TRIF, toll-interleukin 1 receptor domain containing adapter-inducing interferon-␤.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine viral diarrhea viruses (BVDV) are enveloped singlestranded positive-sense RNA viruses comprised of two species, BVDV1 and BVDV2, in the Flaviviridae family (Driskell and Ridpath, 2006;Ridpath et al, 2011). The BVDV genome is approximately 12.5 kb in length and is organized into 12 genes flanked by a Abbreviations: BRDC, bovine respiratory disease complex; BVDV, bovine viral diarrhea virus; CP, cytopathic; HV, high virulence; IFN␥, interferon gamma; IL-6, interleukin 6; LPS, lipopolysaccharide; LV, low virulence; MDM , monocyte derived macrophage; MyD88, myeloid differentiation primary response gene 88; NCP, non-cytpathic; NS5A, non-structural protein 5A; qPCR, quantitative (real-time) polymerase chain reaction; TLR, toll like receptor; TNF␣, tumor necrosis factor alpha; TRIF, toll-interleukin 1 receptor domain containing adapter-inducing interferon-␤.…”
Section: Introductionmentioning
confidence: 99%
“…While BVDV-2 is widespread in the USA and Canada (Pellerin et al, 1994;Fulton et al, 2005;Ridpath et al, 2011), it has been detected more sporadically in Europe, although, is increasingly being identified over the last years (Wakeley et al, 2004;Barros et al, 2006;Jackova et al, 2008;Letellier et al, 2010;Luzzago et al, 2012;Aduriz et al, 2015;Gethmann et al, 2015;Diéguez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, since BVDV-1 and BVDV-2 species are sufficiently different at the antigenic level, a vaccine that protects against one may not protect against the other. For this reason, Ridpath et al (2011) have even proposed using a BVDV vaccine that contains antigens from all subtypes circulating in the target region.…”
Section: Introductionmentioning
confidence: 99%
“…VN results indicated that 66% (35 of 53) of the non-PI cattle were seronegative (≤1:2) on d-1 to all BVDV indicator viruses (Supplementary Table 3). Five of the non-PI cattle (6,25,38,42,43) began the study with VN titers ≥1:16 to all of the indicator viruses and 1 animal (8) had d-1 VN titers ≥1:16 to all 3 of the BVDV-1b indicator viruses (Supplementary Table 3).…”
Section: Virus Neutralizationmentioning
confidence: 99%